The Effect of Moral Reasoning, Retaliation and Negative Emotions on Whistleblowing of Internal Auditors - Mukri, Cotoro; Larasati, Meita (Universitas Muhammadiyah Prof. DR HAMKA., 2023)
The purpose of this study is to investigate the effect of moral reasoning, retaliation and negative emotions (guilt and shame) on the tendency of internal auditors to conduct whistleblowing. This study uses a survey method, with questionnaires distributed to 56 internal auditors working at universities in Yogyakarta. Participants were asked to rate the questionnaire with a five-point Likert scale. All the questionnaires collected were analysed using multiple regression. The results of this study prove empirically that moral reasoning and guilt have a significantly positive influence on the tendency of internal auditors to conduct whistleblowing. Meanwhile, retaliation has a significantly negative effect on the tendency of internal auditors to conduct whistleblowing, but shame does not have a significant effect on the tendency of internal auditors to conduct whistleblowing. This research is expected to provide a basis for organisations to consider establishing whistleblowing systems for fraud and wrongdoing prevention.